Tualang Honey Supplementation Reduces Blood Oxidative Stress Levels/Activities in Postmenopausal Women - Shafin, Nazlahshaniza; Othman, Zahiruddin; Zakaria, Rahimah; Hussain, Nik Hazlina Nik (Hindawi Publishing Corporation, 2014)
his study aimed to investigate the ability of Tualang honey (TH), a phytoestrogen, to reduce blood oxidative stress levels/activities in postmenopausal women and compared the efects with the standard estrogen progestin therapy (EPT). A total of 78 healthy postmenopausal women were randomly assigned to one of two groups; EPT group received Femoston conti 1/5 (1mg 17- estradiol and 5mg dydrogesterone), and TH group, received 20 g of TH supplement daily for 16 weeks. he reduced glutathione to oxidized glutathione ratio (GSH:GSSG), plasma glutathione peroxidase (GPx), catalase (CAT), superoxide dismutase (SOD), and -hydroxynonenal (-HNE) levels/activities were measured at pre- and postinterventions using commercially available kits. he plasma GPx and CAT activities were notably increased, and plasma -HNE level was signiicantly decreased in postmenopausal women who received EPT and TH supplementation. TH supplementation for 16 weeks was able to reduce blood oxidative stress levels/activities of postmenopausal women comparable to those who received EPT. hus, TH has a potential to be used as antioxidant therapy to combat oxidative stress-induced neurodegenerative diseases.his trial is registered with NCT01300676.